Caffeinated coffee consumption and risk of atrial fibrillation in two Spanish cohorts. (4th March 2020) - Bazal, P; Gea, A; Navarro, A M; Salas-Salvadó, J; Corella, D; Alonso-Gómez, A; Fitó, M; Muñoz-Bravo, C; Estruch, R; Fiol, M; Lapetra, J; Serra-Majem, L; et al.
Abstract: Aims: The association between caffeinated coffee consumption and atrial fibrillation remains unclear. Recent studies suggest an inverse association only between a moderate caffeinated coffee consumption and atrial fibrillation, but others have reported no association. The aim of our study was to prospectively assess the association between caffeinated coffee consumption and atrial fibrillation in two Spanish cohorts, one of adults from a general population and another of elderly participants at high cardiovascular risk. Methods and results: We included 18, 983 and 6479 participants from the 'Seguimiento Universidad de Navarra' (SUN) and 'Prevención con Dieta Mediterránea' (PREDIMED) cohorts, respectively. Participants were classified according to their caffeinated coffee consumption in three groups: ≤3 cups/month, 1–7 cups/week, and >1 cup/day. We identified 97 atrial fibrillation cases after a median follow-up of 10.3 years (interquartile range 6.5–13.5), in the SUN cohort and 250 cases after 4.4 years median follow-up (interquartile range 2.8–5.8) in the PREDIMED study. No significant associations were observed in the SUN cohort although a J-shaped association was suggested. A significant inverse association between the intermediate category of caffeinated coffee consumption (1–7 cups/week) and atrial fibrillation was observed in PREDIMED participants with a multivariable-adjusted hazard ratio = 0.53 (95% confidence interval 0.36–0.79) when compared with participants who did not consume caffeinated coffee or did it only occasionally. No association was found for higher levels of caffeinated coffee consumption (>1 cup per day), hazard ratio = 0.79 (95% confidence interval 0.49–1.28). In the meta-analysis of both PREDIMED and SUN studies, the hazard ratio for intermediate consumption of caffeinated coffee was 0.60 (95% confidence interval 0.44–0.82) without evidence of heterogeneity. Similar findings were found for the association between caffeine intake and atrial fibrillation risk. Conclusion: Intermediate levels of caffeinated coffee consumption (1–7 cups/week) were associated with a reduction in atrial fibrillation risk in two prospective Mediterranean cohorts.